Production and evaluation of parathyroid hormone receptor1 ligands with intrinsic or assembled peroxidase domains. Issue 1 (December 2017) - Charest-Morin, Xavier; Poubelle, Patrice; Marceau, François
Abstract Parathyroid hormone (PTH) can be C-terminally extended without significant affinity loss for the PTH1 receptor (PTHR1 ). We developed fusion protein ligands with enzymatic activity to probe PTHR1 s at the cell surface. Two fusion proteins were generated by linking PTH to the N-terminus of either horseradish peroxidase (PTH-HRP) or the genetically modified soybean peroxidase APEX2 (PTH-APEX2). Alternatively, myc-tagged PTH (PTH-myc) was combined with antibodies, some of which HRP-conjugated, in the extracellular fluid. The three PTH-fusion proteins were produced as conditioned mediums (CM) by transfected producer HEK 293a cells. Binding of receptor-bound enzymatic ligands was revealed using widely available substrate/co-substrate systems. The stimulation of recipient HEK 293a expressing PTHR1 s with the PTH-myc/antibodies combination or with PTH-APEX2 supported the histochemical or luminescent detection of recombinant PTHR1 s (TrueBlueTM or luminol-based reagent). The PTH-HRP construction was the most sensitive and supported all tested peroxidase co-substrates (TrueBlueTM, tetramethylbenzidine (TMB), luminol, biotin-phenol with streptavidin-Qdots); the 3 latter schemes identified endogenous PTHR1 in the osteoblastic HOS cell line. The specificity of the fusion protein binding to PTHR1 was determined by its competition with an excess of PTH1–34 . Bifunctional ligands possessing enzymatic activity detect intact receptors with various possible applications, including the screening of drugs that compete for receptor binding.